1994
DOI: 10.1093/nar/22.23.4989
|View full text |Cite
|
Sign up to set email alerts
|

Replication initiation sites are distributed widely in the amplified CHO dihydrofolate reductase domain

Abstract: In previous studies, we utilized a neutral/neutral twodimensional (2-D) gel replicon mapping method to analyze the pattern of DNA synthesis in the amplified dihydrofolate reductase (DHFR) domain of CHOC 400 cells. Replication forks appeared to initiate at any of a large number of sites scattered throughout the 55 kb region lying between the DHFR and 2BE2121 genes, and subsequently to move outward through the two genes. In the present study, we have analyzed this locus in detail by a complementary, neutral/alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
91
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(106 citation statements)
references
References 40 publications
13
91
1
1
Order By: Relevance
“…2C). However, by 100 min, when initiation is maximal in this locus (15,18), a typical composite pattern is detected in this fragment (Fig. 2D).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…2C). However, by 100 min, when initiation is maximal in this locus (15,18), a typical composite pattern is detected in this fragment (Fig. 2D).…”
Section: Resultsmentioning
confidence: 85%
“…1A) (1, 32). In contrast, both neutral/neutral (5) and neutral/alkaline (40) two-dimensional (2-D) gel replicon mapping methods suggest that initiation can occur at any of a large number of sites distributed throughout the 55-kb intergenic region (15,16,18,45).Since it is relatively difficult to accurately compare initiation frequencies at different genomic sites by 2-D gel techniques (5, 36), it is possible that the frequencies of initiation at ori-␤ and ori-␥ have been greatly underestimated (10). Furthermore, 2-D gels are technically challenging, and interpretation is based on a comparison of the patterns obtained with those of well-defined replicons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In several cases initiation has been shown to occur with relatively low efficiency at many different sites in intergenic regions of the genome (47,48). Recent work suggests that human ORC binds preferentially to AT-rich sequences but otherwise has little sequence specificity (49).…”
Section: Discussionmentioning
confidence: 99%
“…However, this zone does not encompass the entire genome, much of which is free of origins that give rise to initiation arcs on N/N 2D-AGE. The fragments that define a contiguous origin-free zone covering the rest of the mitochondrial genome are as follows: in DISCUSSION N/N 2D-AGE has been employed widely since 1987 and is the pre-eminent method for analyzing replication intermediates, including origins of replication (1,30,31); to date, it has proved to be totally reliable. In the present study, extensive analysis of mitochondrial DNA of three mammals revealed a set of overlapping fragments associated with initiation arcs (Figs.…”
Section: Replication Origins Of Rat Mtdna Map To a Broad Region Downsmentioning
confidence: 99%